EXTRACTION ASSOCIATION RULES FROM THE BIOCHEMISTRY PARAMETERS FOR DIAGNOSING HYPERTHYROIDI - Dogan, Sengul; Turkoglu, Ibrahim (Ieee, 2008)
In this study a decision support system has been projected from the biochemistry blood parameters which will be very helpful and will make everything easier for the physicians in the diagnosis of Hyperthyroidi. The system operation is achieved via the association rules structure which is related as one of the data mining techniques. The basic characteristic of the thyroid hormone parameters that is, TSK FT3, FT4, TT3 and TT4 parameters are used in the process of entering the system and finally Hyper(%) results have been evaluated at the end of this process. Data of 472 patients are evaluated in the projected system. The results of the decision support system have completely matched with those of the physicians' decisions.
IEEE 16th Signal Processing and Communications Applications Conference -- APR 20-22, 2008 -- Aydin, TURKEY
Keywords: Knowledge Discovery; Classification Rules; Medical Diagnosis; System